2022
DOI: 10.1093/cei/uxac072
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligases STUB1/CHIP contributes to the Th17/Treg imbalance via the ubiquitination of aryl hydrocarbon receptor in rheumatoid arthritis

Abstract: STIP1-homologous U-Box containing protein 1 (STUB1) is involved in the development of immune pathologies and the regulation of T cell. However, the potential role of STUB1 in the pathogenesis of rheumatoid arthritis (RA), especially in the regulation of T cells, remains elusive. Here we show that STUB1 promotes the imbalance of Th17/Treg cells through non-degradative ubiquitination of AHR. Using Western blot and flow cytometry analysis, we observe that the level of STUB1 was increased in RA patients compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…GO annotation analysis showed ubiquitin mediated proteolysis as the most significantly enriched pathway (p<0.0001) in presence of MG132 (Supplementary figure 6A-C). Previously known substrates such as SQSTM1( 65 ), NPM1( 67 ), PSMD4( 68 ) and HDAC6( 69 ) were identified in this Ub-POD analysis (Supplementary table 8). Applying Ub-POD to CHIP demonstrated that a flexible linker between BirA and the candidate Ub ligase can improve the identification of substrates and that biotin exposure times and stimuli may need to be optimized for a given Ub ligase to identify different sets of substrates.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…GO annotation analysis showed ubiquitin mediated proteolysis as the most significantly enriched pathway (p<0.0001) in presence of MG132 (Supplementary figure 6A-C). Previously known substrates such as SQSTM1( 65 ), NPM1( 67 ), PSMD4( 68 ) and HDAC6( 69 ) were identified in this Ub-POD analysis (Supplementary table 8). Applying Ub-POD to CHIP demonstrated that a flexible linker between BirA and the candidate Ub ligase can improve the identification of substrates and that biotin exposure times and stimuli may need to be optimized for a given Ub ligase to identify different sets of substrates.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, instead of exposing the cells to biotin immediately after transfection, we added biotin to cells 24h after the transfection, along with MG132 (Supplementary Figure 3A). Interestingly, two other known substrates of CHIP, SQSTM1 (also known as p62) (57) and SOD2 (58) were identified (Supplementary Figure 3B, Supplementary table 8) with this short biotin exposure. This change in substrate identification profile depending on the duration of biotin pulse could be due to the different half-lives of various substrates of the CHIP Ub ligase.…”
Section: Employing Ub-pod To Identify Substrates Of U-box Domain Cont...mentioning
confidence: 97%
“…AHR plays a key regulatory role in the differentiation of Treg and Th17 cells. Studies have found that the expression of AhR in CD4 + T cells leads to a signi cant increase in the percentage of Treg and related gene transcripts (including Foxp3, IL-10, and CD39), and a signi cant decrease in the transcription of Th17 cells and related genes (including RORγt, IL-17A, and IL-17F), inducing an imbalance between Th17 and Treg cells [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The new RA pathogenesis hypothesis suggests that Th17/Treg and Th1/Th2 imbalance may be the cause of RA (30) . Initially, Th1 cells have a pathogenic effect on RA.…”
Section: Discussionmentioning
confidence: 99%